2023
DOI: 10.1038/s41598-023-47123-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effectiveness of electric vehicles braking when determining the circumstances of a traffic accident

Andrii Kashkanov,
Andriy Semenov,
Anastasiia Kashkanova
et al.

Abstract: In the vast majority of cases, the braking process is used to prevent traffic accidents. The effectiveness of this process depends on the design and functionality of vehicle braking systems (presence of anti-lock braking system, emergency braking system, preventive safety systems, etc.) and is limited by the amount of frictional forces in contact of tires with the road. The improvement of methodical approaches to evaluating the effectiveness of braking of cars contributes to increasing the accuracy and objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To overcome this problem arising from batteries, the first work to be done brings with it the necessity of using energy in the most efficient way in EVs. Scientific studies conducted for this purpose have shown that regenerative braking can increase the range of EVs by 20-30% [11][12][13]. However, electrical conditions such as fast charging and frequent charging, which we can see as the reason for this situation, cause negative effects on the vehicle battery and cause the battery pack or battery cells to deteriorate [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem arising from batteries, the first work to be done brings with it the necessity of using energy in the most efficient way in EVs. Scientific studies conducted for this purpose have shown that regenerative braking can increase the range of EVs by 20-30% [11][12][13]. However, electrical conditions such as fast charging and frequent charging, which we can see as the reason for this situation, cause negative effects on the vehicle battery and cause the battery pack or battery cells to deteriorate [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Peter Kožuch et al [1] evaluated the braking systems of intercity buses through both dynamic and stationary tests, finding that dynamic tests, although more complex, provide a more accurate reflection of real-world capabilities compared to the faster and safer stationary tests. Meanwhile, Andrii Kashkanov and his colleagues [2] presented a mathematical model to improve the accuracy of traffic accident analysis by estimating vehicle stopping distances, which integrates different methodological approaches and shows promising validation results. In another study by A.…”
mentioning
confidence: 99%